Encyclopedia of ZEMCH Research and Development - Noguchi, Masa; Frattari, Antonio; Formoso, Carlos Torres; Altan, Haşim; Onyango, John Odhiambo; Kim, Jun-Tae; Anissa Tabet Aoul, Kheira; Amirkhani, Mehdi; Wilkinson, Sara Jane; Bantanur, Shaila (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The concept of the 'Zero Energy Mass Custom Home' or ZEMCH is emerging with the aim of exploring opportunities to make our built environment more socially, economically, environmentally, and humanly sustainable. The built environment is indeed a system of energy and environment that is occupied by the masses, embracing diverse cultural and economic backgrounds. Today, the United Nations articulates the 17 Sustainable Development Goals that reflect necessary global actions for humanity and the planet. In view of these agendas, the delivery of built environments is becoming more demanding and complex than ever, and it is now required that developers accommodate the social, economic, environmental, and human dimensions of these sustainability challenges. This volume encompasses a wide spectrum of ZEMCH research and development knowledge that concerns design engineering, construction management, material innovation, renewable energy technology, and community planning.